The Effect of CSR on Buyback Decisions with Brand Image Mediation and Credibilitys Merek: Case of Wardah Halal Cosmetics in Indonesia - Marsha Chikita Fawzi; Chico Adhibaskara Ekananda Hindarto (Jurnal Ilmu Manajemen & Ekonomika, 2023)
Corporate social responsibility (CSR) is becoming one of the most critical challenges, where companies need to survive in an increasingly competitive business world. Therefore, the research conducted in this study is an investigation effort on the impact of customer CSR perception on repeat purchase intent, mediated by brand image and brand credibility, with the aim of uncovering the benefits of CSR values that have been applied within the company. This study used a purely quantitative approach, in collecting data on 290 people with female gender who had become customers of Wardah halal cosmetics, using questionnaires through online surveys. Smart PLS-SEM 4.0 software is used to analyze data. The results showed that perceptions from customers showed that the CSR activities produced by the company did not directly have a significant effect on the decision to repurchase its products. However, CSR significantly has a direct influence on its mediation variables, namely: (1) Brand Image; and (2) Brand Credibility. The results obtained provide an important reference for the academic world in terms of conducting empirical research on this subject, as well as benefits for marketers and company managers who want to develop their marketing strategies using CSR elements for the expected improvement of sustainable business development.